Parental Stress and Parental Ratings of Behavioral Problems of Enuretic Children - Roccella, Michele; Smirni, Daniela; Smirni, Pietro; Precenzano, Francesco; Operto, Francesca Felicia; Lanzara, Valentina; Quatrosi, Giuseppe; Carotenuto, Marco (Frontiers in Neurology, 2019)
Background: Primary monosymptomatic nocturnal enuresis (PMNE) may have a stressful impact on the everyday life of children and parents, and it may represent a cumulative stress factor increasing feelings of “learned helplessness.” Methods: The current study investigated parental stress in a group of parents (n = 330) of children affected by PMNE, compared to a group of parents (n = 330) of typical developing children (TDC). In addition, the study evaluated whether parents of PMNE children experience more emotional, social, and behavioral problems in their children, compared to parents of TDC. Finally, the study correlated frequency of enuresis with stress values and Child Behavior Checklist (CBCL) subscales and total stress with CBCL. Both groups were given The Parental Stress Inventory-Short Form (PSI-SF) and the Child Behavior Checklist (CBCL). Results: Parents of PMNE children showed significantly higher stress level than parents of TDC. Nocturnal enuresis, as a demanding clinical condition difficult to control, represents a relevant stress factor. Mothers appeared as more vulnerable to stress than fathers. Parents of PMNE children reported higher behavioral and emotional problems, compared to reports of parents of TDC. PMNE children appeared to their parents as having lower competency in social activities, school performance, and social relationships than TDC. Moreover, they were rated as more withdrawn, anxious-depressed, more aggressive, inattentive, and with more somatic complaints than healthy children. It was always the mother who rated a significantly higher number of emotional, social, and behavioral problems compared to fathers. Correlational analysis showed that the higher the frequency of enuresis, the greater the parental stress level, the lower the social activities, school performance and relational competencies and the higher the emotional, social and behavioral problems in children, according to the parents' evaluations. The greater the parental stress level, the lower the competencies rated and the higher the behavioral problems detected by parents. Conclusion: The physicians who deal with PMNE children have taken into account the stressful role and emotional dimensions of this clinical condition, both for children and mothers, in order to improve clinical management. Psychological support is needed for parents, and mothers especially, for a more functional stress management related to the PMNE.